2008
DOI: 10.1002/hc.20387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic aminomethylphosphonates and aminomethyl‐arylphosphinic acids by an efficient microwave‐mediated phospha‐mannich approach

Abstract: Microwave‐assisted condensation of 1,3,‐2‐dioxaphosphinane 2‐oxide (1), paraformaldehyde and secondary amines including 5‐ and 6‐membered N‐heterocycles at 55°C gave cyclic aminomethylphosphonates (2), whereas an analogous reaction involving dibenzo[c.e][1,2]oxaphosphinane 2‐oxide (3) resulted in the corresponding aminomethyl‐2‐(2′‐hydroxybiphenyl)phosphinic acids (4) as a consequence of a hydrolytic ring opening following the condensation. © 2008 Wiley Periodicals, Inc. Heteroatom Chem 19:207–210, 2008; Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…A cyclic H-phosphonate, 1,3,2-dioxaphosphorine oxide 2 was also utilized in the phospha-Mannich reactions (Scheme 2). 10 In this case, the use of a solvent prevented the formation of by-products.…”
Section: Methodsmentioning
confidence: 97%
“…A cyclic H-phosphonate, 1,3,2-dioxaphosphorine oxide 2 was also utilized in the phospha-Mannich reactions (Scheme 2). 10 In this case, the use of a solvent prevented the formation of by-products.…”
Section: Methodsmentioning
confidence: 97%
“…It was also found that the syntheses can be carried out without the use of any solvent [27]. Applying heterocyclic amines or >P(O)H species, the α-aminophosphonates and α-aminophosphine oxides synthesized included N-heterocyclic [28] and P-heterocyclic derivatives [29].…”
Section: Methodsmentioning
confidence: 99%
“…1,3,2-dioxaphosphorine oxide) led to N-heterocyclic [73] and P-heterocyclic [74] α-aminophosphonates (51, Y = EtO and 52) and α-aminophosphine oxides (51, Y = Ph) (Schemes 3.36 and 3.37). (53), the heterocyclic ring underwent ring opening by reaction with water formed in the condensation to result in end-product 55 (Scheme 3.38) [74].…”
Section: The Addition Of >P(o)h Species To Carbonyl-compoundsmentioning
confidence: 99%